30th Annual GP2A Medicinal Chemistry Conference - Niamh M. O'Boyle; Jean-Jacques Helesbeux; Mary J. Meegan; Astrid Sasse; Elizabeth O'Shaughnessy; Alina Qaisar; Aoife Clancy; Florence McCarthy; Pascal Marchand (MDPI AG, 2023)
The Group for the Promotion of Pharmaceutical Chemistry in Academia (GP2A) held their 30th annual conference in August 2022 in Trinity College Dublin, Ireland. There were 9 keynote presentations, 10 early career researcher presentations and 41 poster presentations.